More Frequent Clinic Visits Are Associated with Improved Outcomes for Children with NAFLD - Carol Lam; Robert Bandsma; Simon Ling; Marialena Mouzaki (Canadian Journal of Gastroenterology and Hepatology)
Objective. Adult data suggest that frequent monitoring of patients with nonalcoholic fatty liver disease (NAFLD) may be associated with improved outcomes. The optimal frequency of outpatient visits for the management of pediatric NAFLD remains unknown. Study Design. In this retrospective study, two cohorts of patients with NAFLD, one followed on a yearly basis and one followed on 3-month intervals, were included. Both received similar advice regarding lifestyle changes. Primary outcome was change in BMI z-scores over a year. Secondary outcomes were the change in serum transaminases and markers of metabolic dysregulation. Results. Fifty-six patients were included (28 per group). The majority (71%) were male with a mean (±SD) age of 12.2 (±2.7) years. At baseline, there were no differences in BMI z-scores (2.8 versus 2.9; p=0.72) and ALT levels (101 versus 100 U/L; p=0.95) between the groups (yearly versus three-month, resp.). Twelve months later, those followed on a 3-month basis demonstrated a significant decrease in BMI (net BMI z-score change = −0.06; p=0.37), accompanied by a significant improvement in serum ALT (−25 U/L; p<0.01) and AST (−13 U/L; p=0.03) levels. There were no differences in fasting lipid profiles. Conclusion. Frequent clinic visits are associated with improved outcomes in pediatric NAFLD.